Perancangan Protokol Komunikasi untuk JSN (Jaringan Sensor Nirkabel) pada Kampus Hijau - Nurazizah Nurazizah; Oky Dwi Nurhayati; Eko Didik Widianto (Jurnal Teknologi dan Sistem Komputer, 2016)
Environmental conditions in a large area often requires monitoring. For example, in the case of greenhouse used for experimental research cultivation, fertilization experiment, experiment plant resistance, tissue culture experiments, experimental planting of crops in the off-season, the necessary equipment to monitor and control the environmental conditions in order to suit the characteristics of the environment is needed. The size of area to be monitored, making the need for the spread of monitoring equipment at some point so that monitoring environmental conditions can include all the desired area. This is the basis for the design of communication protocols for WSN (wireless sensor networks) on a green campus. The system consists of hardware that is assembled to the process of measuring PM2.5, CO, NO2, HC, light intensity, temperature, and humidity. The system is divided into several sections, hereinafter referred to node. Node on this system can be divided into two functions, namely a sensor node and coordinator node. There are two sensor nodes that will work for data collection in a separate area and sends the data to the coordinator node. Communication between nodes is done using nRF905 module. The design of communication protocols that are designed to connect between the coordinator node to sensor node is able to run well. It makes the system capable of monitoring temperature and humidity via a web service, so that can know the condition of PM2.5, CO, NO2, HC, the intensity of light, temperature and humidity at some point in the range of more than 100 meters.